Remediation of atrazine contaminated soil by microwave activated persulfate system: Performance, mechanism and DFT calculation. (1st May 2023) - Qu, Jianhua; Liu, Ruixin; Bi, Xuewei; Li, Zhuoran; Li, Kaige; Hu, Qi; Zhang, Xinru; Zhang, Guangshan; Ma, Shouyi; Zhang, Ying
Abstract: Effective remediation of pesticide-contaminated sites is challenging due to high concentrations of pollutants with complete habitat destruction. Herein, microwave (MW)-activated persulfate (PS) system was proposed for remediation of organochlorine pesticide contaminated soil with atrazine (ATZ) as representation. The results revealed that the MW/PS system could achieve 97.9% of ATZ (50 mg/kg) degradation after treatment of 60 min, superior to that by conventional heat-activated PS. And more excellent degradation performance was identified in relatively higher microwave temperature (80 °C) with appropriate PS concentration (24 mmol/L), MW power (400 W) and water-soil ratio (1:1). Moreover, the MW/PS system possessed high tolerance to co-existing substances including C l −, H C O 3 − and H 2 P O 4 −, and appropriate organic substance content favored ATZ degradation in soil. Reactive oxygen species consisting of S O 4 −, O H, O 2 − and 1 O2 contributed to ATZ decomposition, among which O 2 ∙ − played a principal role. The ATZ degradation pathway was then elucidated by combination of HPLC/MS spectra and DFT calculations, and ATZ overall toxicity was effectively alleviated in MW/PS system in term of toxicity assessment. Additionally, the MW/PS system presented high-performance degradation on such organochlorine pesticides as trichloro ethylene, tetrachloride, hexachlorobenzene and chlordane, suggesting great potentials of this system for remediation of organochlorine pesticides contaminated sites. Graphical abstract: Image 1